Learning from 50 Years of Aboriginal Alcohol Programs Beating the Grog in Australia - d'Abbs, Peter (Springer Nature, 2023)
This open access book deals with community-based attempts on the part of Aboriginal communities and groups in Australia to address harms arising from alcohol misuse. Alcohol-related harms are viewed as both a product of colonisation and dispossession and a contributor to ongoing social, economic and health-related disadvantage, both in Australia and in other countries with colonised Indigenous populations, such as Canada, the US and New Zealand. This book contributes to an evidence-base by bringing together a selection of existing Australian documents considered by the editors to have continuing relevance to all those concerned with dealing with alcohol-related harms among Aboriginal peoples, These are contextualised in original chapters that recount key events, ideas, and programs. The book is a practical resource for all people and groups concerned with addressing Aboriginal and Torres Strait Islander alcohol-related harms, both at the community level and at the level of policy-making and administration.